On duality in multiobjective semi-infinite optimization. (3rd August 2017) - Guerra-Vázquez, Francisco; Rückmann, Jan-J.
Abstract: In this paper, we consider multiobjective semi-infinite optimization problems which are defined in a finite-dimensional space by finitely many objective functions and infinitely many inequality constraints. We present duality results both for the convex and nonconvex case. In particular, we show weak, strong and converse duality with respect to both efficiency and weak efficiency. Moreover, the property of being a locally properly efficient point plays a crucial role in the nonconvex case.